Geometrical nonlinearities on the static analysis of highly flexible steel cable-stayed bridges - Freire, A. M. S. (2006)
An evaluation of the importance of geometrically nonlinear effects on the structural static analysis of steel cable-stayed bridges is presented. A finite element model is analyzed using linear, pseudo-linear and nonlinear methods. The pseudo-linear approach is based on the modified elastic modulus. The nonlinear analysis involves cable sag, large displacement and beam-column effects. The results confirm that both cable sag and large displacement originate the most important nonlinear effects in those structures. Beam-column effects are irrelevant for service loads. Both the pseudo-linear approach and the modified modulus element prove to be very limited or even inappropriate.